(untitled) (Mustansiria Dental Journal, 2018)
The mental foramen is the opening of the short mental canal, through which the mental nerve the terminal branch of the inferior alveolar nerve exits, knowing the exact position of the mental foramen is essential in oral surgical procedures. This study determines this position in a selected Iraqi population. 240 panoramic radiographs of Iraqi population selected from three different oral and maxillofacial centers to identify the normal range of position of the mental foramen, both horizontal and vertical position were studied, radiographs with any errors or taken for patients not co inside with our criteria were excluded. In horizontal position , 51.31% were found apical to the lower second premolar , 43.64% between the first and second premolars, 3.07% were found between second premolar and lower first molar, 1.09% were found apical to the lower first premolar, 0.87% were found between lower canine and lower first premolar. In vertical position,60.08% were found inferior to the apex of the related tooth, 36.84% were found within the apex of the related tooth while 3.07% were found superior to the apex. The mental foramen can be found anywhere from lower canine to the lower first molar, although 94.95% of the studied radiographs showed that mental foramen was located either between the lower premolars or at the apex of the second premolar.